Self-review in early childhood education : "what's it all about?" : a thesis presented in partial fulfilment of the requirements for the degree of Masters of Education at Massey University - Collins, Sandra May (Massey University, 2007)
An increased focus on self-review in early childhood education (ECE) in New Zealand has been influenced by the educational and political context of the past 15 years. The requirement for early childhood services to undertake internal review has been a feature of the regulatory framework since 1998 (and the requirement to undertake programme review has been in place since 1990). The Education Review Office (ERO) has given more emphasis to self-review through changes to its external review methodology since 1998, and self-review has been an area of national interest in all early childhood education reviews since 2005. Through the analysis of a sample of ERO reports, this research seeks to understand how external review has shaped and influenced thinking and practice associated with self-review in ECE services. The analysis of ERO's findings about self-review, as reported in accountability review reports (undertaken between 1998-2002) and education review reports (undertaken in 2005), revealed a complex milieu of activity that spanned everything that those who are involved in early childhood education services do as part of the operation of their service. This research also examined the political and educational contexts in which self-review understandings and practiccs have developed in early childhood services. The review of the literature illuminates how self-review has been defined, researched and practiced. The educational reforms that introduced charters and concepts of accountability and self-management to education in New Zealand in the late 1980s and early 1990s were a feature of the early childhood education landscape that gave rise to expectations of improved quality and increased accountability. This research explored the shifts that have taken place in ECE serviccs as reported by ERO and discussed in the context of the time. The relationship between self-review and external review is identified as needing revisiting and substantive discussion to explore ways that these two evaluative processes can be truly complementary.
Keywords: New Zealand; Early childhood education; Evaluation